Thermally conductive composition and thermally conductive member

By adjusting the concentration and Raman strength ratio of the hydrogen silyl group and combining with the platinum group curing catalyst, the cross-linking structure of the thermally conductive composition is solved in the prior art, and the softness of the thermally conductive composition at high temperatures is reduced and the thermal resistance increases in the prior art. The problem of this method achieves stable performance above 150°C.

CN119256062APending Publication Date: 2025-01-03SEKISUI CHEMICAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040751.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-06-16
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

When the conventional thermally conductive silicone composition is used in a high temperature environment of 150°C or above, the softness decreases and the problem of peeling and thermal resistance increase.

Method used

By adjusting the concentration and Raman strength ratio of the hydrosilyl group in the components (B) and (C), combined with the platinum group curing catalyst, the crosslinking structure of the thermally conductive composition is controlled to ensure that the moderate hardness is maintained at 150°C. and softness.

Benefits of technology

A thermally conductive member that is not easy to peel off in an environment above 150°C and suppresses a rise in thermal resistance, thereby improving the reliability and heat resistance of the composition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005136144480000121
    Figure BDA0005136144480000121
  • Figure BDA0005136144480000241
    Figure BDA0005136144480000241
  • Figure BDA0005136144480000251
    Figure BDA0005136144480000251
Patent Text Reader

Abstract

A thermally conductive composition comprising (A) an organopolysiloxane having two or more alkenyl groups, (B) an organohydrogenpolysiloxane having two hydrosilyl groups, (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups, (D) an organopolysiloxane having one alkenyl group or methacryloyl group, (E) a thermally conductive filler, and (F) a platinum group curing catalyst, the ratio p2 / p1 of the Raman intensity p1 at 2160 cm <-1 > to the Raman intensity p2 at 2130 cm <-1 > in a Raman spectroscopic spectrum is greater than 3.00, and the E-type hardness E2 is less than 70 after standing at 25 DEG C for 24 hours and further standing at 150 DEG C for 250 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermally conductive composition and a thermally conductive member. Background Art

[0002] Thermally conductive compositions that are curable and in liquid form are well known, and are used, for example, as thermally conductive components such as heat dissipation gap fillers that are filled between a heating element and a heat dissipation element and then cured to form a cured product to transfer heat generated by the heating element to the heat dissipation element. Conventionally, as thermally conductive compositions, silicone thermally conductive compositions containing organopolysiloxane and a thermally conductive filler have been widely used.

[0003] In recent years, the production volume of electric vehicles has been steadily increasing, and the electricization has been progressing for the purpose of improving fuel efficiency and safety. The demand for automatic assembly of on-board electrical components has increased, and the demand for liquid heat dissipation gap fillers that can be used in complex shapes has increased.

[0004] In addition, for recent cars, fuel efficiency has become one of the important differentiation factors, and the body weight is required to be as light as possible. The development of lightweight and miniaturized automotive electrical components is no exception. However, if the electrical components are miniaturized, the heat generation per unit volume, that is, the heat density, increases. Therefore, the heat dissipation gap filler is required to be reliable enough to be used for a long time without reducing the performance such as thermal conductivity.

[0005] Various studies have been conducted on the reliability of thermally conductive compositions. For example, Patent Document 1 discloses a thermally conductive silicone composition comprising (A) an organopolysiloxane having at least two alkenyl groups in one molecule, (B) a hydrolyzable dimethylpolysiloxane having trifunctional groups at one terminal, (C) a thermally conductive filler, (D) an organohydrogenpolysiloxane having a hydrosilyl group at the terminal, (E) an organohydrogenpolysiloxane having at least two hydrosilyl groups in one molecule, and (F) a platinum catalyst.

[0006] Patent Document 1 shows that by adjusting the ratio of the hydrosilyl group to the alkenyl group in the components (A), (D), and (E) to within a predetermined range, the occurrence of pumping out and peeling during the hot and cold cycle assumed in actual operation can be suppressed, and the increase in thermal resistance can also be suppressed. However, in Patent Document 1, the surface temperature of heat-generating electronic components such as IC packages is assumed to be around 120°C, and there is no mention of reliability at higher temperatures.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent No. 6079792 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, in recent cars, in order to improve the comfort of the cabin, it is required to make the interior space wider. When studying the layout of body parts, priority is often given to large and heavy core parts such as engines and electric motors, and relatively small and light parts such as electrical components sometimes have to be arranged in the remaining space. As a result, some electrical components are placed in the engine room, near the electric motor, etc., and are sometimes exposed to high temperature environments above 150°C, and heat dissipation gap fillers are sometimes used at high temperatures. However, the heat dissipation gap fillers formed by conventional thermally conductive silicone thermally conductive compositions have reduced flexibility if used for a long time in a high temperature environment above 150°C, and peeling occurs relative to the heating element and the heat dissipation element, making it difficult to suppress the increase in thermal resistance.

[0012] It should be noted that, for conventional thermally conductive compositions having an organopolysiloxane having an alkenyl group and an organohydrogenpolysiloxane having a hydrosilyl group as the main component of the silicone resin, in order to increase the flexibility, it is also conceivable to increase the molecular chain length between crosslinks, reduce the functional group concentration, and make the crosslinking points sparse. However, if the molecular chain length between crosslinks is increased, the molecular weight of the silicone resin increases and the viscosity becomes high, resulting in a problem that a large amount of thermally conductive filler cannot be filled.

[0013] The present invention has been made in view of the above problems, and aims to provide a thermally conductive composition that can provide a thermally conductive member that is less likely to peel off from a heating element, a radiator, etc. and has a suppressed increase in thermal resistance even in a usage environment of 150° C. or higher.

[0014] Means for solving problems

[0015] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by adjusting the concentration of the hydrosilyl group of the components (B) and (C) to a predetermined range, or adjusting the Raman intensities p1 and p2 derived from the hydrosilyl group in the Raman spectroscopic spectrum to satisfy a predetermined relationship, and controlling the type E hardness (E2) to a certain value or less after leaving the composition at 25°C for 24 hours and at 150°C for 250 hours, thereby completing the following invention. That is, the present invention provides the following [1] to

[23] .

[0016] [1] A thermally conductive composition comprising

[0017] (A) an organopolysiloxane having two or more alkenyl groups,

[0018] (B) an organohydrogenpolysiloxane having two hydrosilyl groups,

[0019] (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups,

[0020] (D) an organopolysiloxane having one alkenyl group or methacryloyl group,

[0021] (E) thermally conductive filler material, and

[0022] (F) a platinum group curing catalyst,

[0023] 2160cm in Raman spectra -1 The Raman intensity at p1 and 2130 cm -1 The Raman intensity p2 at satisfies the following relationship (1-1):

[0024] After being left at 25°C for 24 hours and further left at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2).

[0025] p2 / p1>3.00 (1-1)

[0026] E2<70 (2)

[0027] [2] A thermally conductive composition comprising

[0028] (A) an organopolysiloxane having two or more alkenyl groups,

[0029] (B) an organohydrogenpolysiloxane having two hydrosilyl groups,

[0030] (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups,

[0031] (D) an organopolysiloxane having one alkenyl group or methacryloyl group,

[0032] (E) thermally conductive filler material, and

[0033] (F) a platinum group curing catalyst,

[0034] The above-mentioned components (B) and (C) are contained so as to satisfy the relationship of the following formula (1-2):

[0035] After being left at 25°C for 24 hours and further left at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2).

[0036] b / (b+c)>0.45 (1-2)

[0037] (In formula (1-2), b is the concentration of the hydrosilyl groups contained in component (B), and c is the concentration of the hydrosilyl groups contained in component (C).)

[0038] E2<70 (2)

[0039] [3] A thermally conductive composition comprising

[0040] (A) an organopolysiloxane having two or more alkenyl groups,

[0041] (B) an organohydrogenpolysiloxane having two hydrosilyl groups,

[0042] (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups,

[0043] (D) an organopolysiloxane having one alkenyl group or methacryloyl group,

[0044] (E) thermally conductive filler material, and

[0045] (F) a platinum group curing catalyst,

[0046] The thermally conductive composition is composed of a first agent and a second agent.

[0047] The first agent comprises at least one of the components (A) and (D) and the component (F), and does not comprise the component (B) and the component (C).

[0048] The second agent comprises the component (B) and the component (C), and does not comprise the component (F).

[0049] 2160cm in Raman spectra -1 The Raman intensity at p1 and 2130 cm -1 The Raman intensity p2 at satisfies the following relationship (1-1):

[0050] After the first agent and the second agent are mixed and left at 25°C for 24 hours and further left at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2).

[0051] p2 / p1>3.00 (1-1)

[0052] E2<70 (2)

[0053] [4] A thermally conductive composition comprising

[0054] (A) an organopolysiloxane having two or more alkenyl groups,

[0055] (B) an organohydrogenpolysiloxane having two hydrosilyl groups,

[0056] (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups,

[0057] (D) an organopolysiloxane having one alkenyl group or methacryloyl group,

[0058] (E) thermally conductive filler material, and

[0059] (F) a platinum group curing catalyst,

[0060] The thermally conductive composition is composed of a first agent and a second agent.

[0061] The first agent comprises at least one of the components (A) and (D) and the component (F), and does not comprise the component (B) and the component (C).

[0062] The second agent comprises the component (B) and the component (C), and does not comprise the component (F).

[0063] The above-mentioned components (B) and (C) are contained so as to satisfy the relationship of the following formula (1-2):

[0064] After the first agent and the second agent are mixed and left at 25°C for 24 hours and further left at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2).

[0065] b / (b+c)>0.45 (1-2)

[0066] (In formula (1-2), b is the concentration of hydrosilyl groups in component (B), and c is the concentration of hydrosilyl groups in component (C).)

[0067] E2<70 (2)

[0068] [5] A thermally conductive composition comprising

[0069] (A) an organopolysiloxane having two or more alkenyl groups,

[0070] (B) an organohydrogenpolysiloxane having two hydrosilyl groups,

[0071] (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups,

[0072] (D) an organopolysiloxane having one alkenyl group or methacryloyl group,

[0073] (E) thermally conductive filler material, and

[0074] (F) a platinum group curing catalyst,

[0075] The Raman intensity p1 at 2160 cm-1 and the Raman intensity p2 at 2130 cm-1 in the Raman spectrum satisfy the relationship of the following formula (1-1), or the above-mentioned (B) component and (C) component are contained so as to satisfy the relationship of the following formula (1-2),

[0076] After being left at 25°C for 24 hours and further left at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2).

[0077] p2 / p1>3.00 (1-1)

[0078] b / (b+c)>0.45 (1-2)

[0079] (In formula (1-2), b is the concentration of the hydrosilyl groups contained in component (B), and c is the concentration of the hydrosilyl groups contained in component (C).)

[0080] E2<70 (2)

[0081] [6] The thermally conductive composition according to [5] above, which is composed of a combination of a first agent and a second agent,

[0082] The first agent comprises at least one of the components (A) and (D) and the component (F), and does not comprise the component (B) and the component (C).

[0083] The second agent contains the component (B) and the component (C), and does not contain the component (F).

[0084] [7] The thermally conductive composition according to any one of [1] to [6] above, further comprising (G) an organopolysiloxane having no addition reactive group.

[0085] [8] The thermally conductive composition according to [7] above, wherein the component (G) comprises (G-2) an organopolysiloxane having at least one alkoxy group.

[0086] [9] The thermally conductive composition according to any one of [1] to [8], wherein the relationship between the type E hardness E1 after being left at 25° C. for 24 hours and the above E2 satisfies the following formula (3).

[0087] 1.4≤E2 / E1≤3.5 (3)

[0088]

[10] The thermally conductive composition according to any one of [1] to [9] above, wherein the component (D) is an organopolysiloxane having one methacryloyl group.

[0089]

[11] The thermally conductive composition according to any one of [1] to

[10] above, wherein the total content of alkenyl groups and methacryloyl groups is 5.0 μmol / g or less.

[0090]

[12] The thermally conductive composition according to any one of [1] to

[11] above, wherein the content H of the hydrosilyl groups and the total content Vi of the alkenyl groups and the methacryloyl groups satisfy the relationship of the following formula (4).

[0091] 0.85≤H / Vi≤1.1·(4)

[0092]

[13] A thermally conductive member obtained by curing the thermally conductive composition according to any one of [1] to

[12] above.

[0093]

[14] A first agent that can be used as a thermally conductive composition by mixing with a second agent, the thermally conductive composition comprising

[0094] (A) an organopolysiloxane having two or more alkenyl groups,

[0095] (B) an organohydrogenpolysiloxane having two hydrosilyl groups,

[0096] (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups,

[0097] (D) an organopolysiloxane having one alkenyl group or methacryloyl group,

[0098] (E) thermally conductive filler material, and

[0099] (F) a platinum group curing catalyst,

[0100] The first agent comprises at least one of the components (A) and (D) and the component (F), and does not comprise the component (B) and the component (C).

[0101] The first agent is combined with the second agent to reduce the Raman spectrum to 2160 cm -1 The Raman intensity at p1 and 2130 cm -1 The Raman intensity p2 at satisfies the following relationship (1-1):

[0102] After the first agent and the second agent are mixed and left at 25°C for 24 hours and further left at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2).

[0103] p2 / p1>3.00 (1-1)

[0104] E2<70 (2)

[0105]

[15] A second agent that can be used as a thermally conductive composition by mixing with the first agent, the thermally conductive composition comprising

[0106] (A) an organopolysiloxane having two or more alkenyl groups,

[0107] (B) an organohydrogenpolysiloxane having two hydrosilyl groups,

[0108] (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups,

[0109] (D) an organopolysiloxane having one alkenyl group or methacryloyl group,

[0110] (E) thermally conductive filler material, and

[0111] (F) a platinum group curing catalyst,

[0112] The second agent comprises the component (B) and the component (C), and does not comprise the component (F).

[0113] The second agent is combined with the first agent to reduce the Raman spectrum to 2160 cm -1 The Raman intensity at p1 and 2130 cm -1 The Raman intensity p2 at satisfies the following relationship (1-1):

[0114] After the first agent and the second agent are mixed and left at 25°C for 24 hours and further left at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2).

[0115] p2 / p1>3.00 (1-1)

[0116] E2<70 (2)

[0117]

[16] A first agent that can be used as a thermally conductive composition by mixing with a second agent, the thermally conductive composition comprising

[0118] (A) an organopolysiloxane having two or more alkenyl groups,

[0119] (B) an organohydrogenpolysiloxane having two hydrosilyl groups,

[0120] (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups,

[0121] (D) an organopolysiloxane having one alkenyl group or methacryloyl group,

[0122] (E) thermally conductive filler material, and

[0123] (F) a platinum group curing catalyst,

[0124] The first agent comprises at least one of the components (A) and (D) and the component (F), and does not comprise the component (B) and the component (C).

[0125] The thermally conductive composition contains the component (B) and the component (C) so as to satisfy the relationship of the following formula (1-2).

[0126] After the first agent and the second agent are mixed and left at 25°C for 24 hours and further left at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2).

[0127] b / (b+c)>0.45 (1-2)

[0128] (In formula (1-2), b is the concentration of hydrosilyl groups in component (B), and c is the concentration of hydrosilyl groups in component (C).)

[0129] E2<70 (2)

[0130]

[17] A second agent that can be used as a thermally conductive composition by mixing with the first agent, the thermally conductive composition comprising

[0131] (A) an organopolysiloxane having two or more alkenyl groups,

[0132] (B) an organohydrogenpolysiloxane having two hydrosilyl groups,

[0133] (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups,

[0134] (D) an organopolysiloxane having one alkenyl group or methacryloyl group,

[0135] (E) thermally conductive filler material, and

[0136] (F) a platinum group curing catalyst,

[0137] The second agent comprises the component (B) and the component (C), and does not comprise the component (F).

[0138] The above-mentioned components (B) and (C) are contained so as to satisfy the relationship of the following formula (1-2):

[0139] After the first agent and the second agent are mixed and left at 25°C for 24 hours and further left at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2).

[0140] b / (b+c)>0.45 (1-2)

[0141] (In formula (1-2), b is the concentration of hydrosilyl groups in component (B), and c is the concentration of hydrosilyl groups in component (C).)

[0142] E2<70 (2)

[0143]

[18] A first agent that can be used as a thermally conductive composition by mixing with a second agent, the thermally conductive composition comprising

[0144] (A) an organopolysiloxane having two or more alkenyl groups,

[0145] (B) an organohydrogenpolysiloxane having two hydrosilyl groups,

[0146] (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups,

[0147] (D) an organopolysiloxane having one alkenyl group or methacryloyl group,

[0148] (E) thermally conductive filler material, and

[0149] (F) a platinum group curing catalyst,

[0150] The first agent comprises at least one of the components (A) and (D) and the component (F), and does not comprise the component (B) and the component (C).

[0151] The thermally conductive composition contains the component (B) and the component (C) so as to satisfy the relationship of the following formula (1-2), or the first agent is combined with the second agent so that the Raman intensity p1 at 2160 cm-1 and the Raman intensity p2 at 2130 cm-1 in the Raman spectrum satisfy the relationship of the following formula (1-1),

[0152] After the first agent and the second agent are mixed and left at 25°C for 24 hours and further left at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2).

[0153] p2 / p1>3.00 (1-1)

[0154] b / (b+c)>0.45 (1-2)

[0155] (In formula (1-2), b is the concentration of hydrosilyl groups in component (B), and c is the concentration of hydrosilyl groups in component (C).)

[0156] E2<70 (2)

[0157]

[19] A second agent that can be used as a thermally conductive composition by mixing with the first agent, the thermally conductive composition comprising

[0158] (A) an organopolysiloxane having two or more alkenyl groups,

[0159] (B) an organohydrogenpolysiloxane having two hydrosilyl groups,

[0160] (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups,

[0161] (D) an organopolysiloxane having one alkenyl group or methacryloyl group,

[0162] (E) thermally conductive filler material, and

[0163] (F) a platinum group curing catalyst,

[0164] The second agent comprises the component (B) and the component (C), and does not comprise the component (F).

[0165] The above-mentioned components (B) and (C) are contained so as to satisfy the relationship of the following formula (1-2), or by being combined with the above-mentioned first agent, the Raman intensity p1 at 2160 cm-1 and the Raman intensity p2 at 2130 cm-1 in the Raman spectroscopic spectrum satisfy the relationship of the following formula (1-1),

[0166] After the first agent and the second agent are mixed and left at 25°C for 24 hours and further left at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2).

[0167] p2 / p1>3.00 (1-1)

[0168] b / (b+c)>0.45 (1-2)

[0169] (In formula (1-2), b is the concentration of hydrosilyl groups in component (B), and c is the concentration of hydrosilyl groups in component (C).)

[0170] E2<70 (2)

[0171]

[20] A method of mixing the first agent described in

[14] ,

[16] or

[18] above with the second agent.

[0172]

[21] A method of mixing the second agent described in

[15] ,

[17] or

[19] above with the first agent.

[0173]

[22] Use of the first agent described in

[14] ,

[16] or

[18] in a two-component thermally conductive composition.

[0174]

[23] Use of the second agent described in

[15] ,

[17] or

[19] above in a two-component thermally conductive composition.

[0175] Effects of the Invention

[0176] According to the thermally conductive composition of the present invention, it is possible to obtain a thermally conductive member which is unlikely to peel off from a heating element, a radiating element, etc. even in a usage environment of 150° C. or higher and has a suppressed increase in thermal resistance. DETAILED DESCRIPTION

[0177] [Thermal conductive composition]

[0178] Hereinafter, the thermally conductive composition of the present invention will be described in detail.

[0179] The thermally conductive composition of the present invention comprises the following components (A) to (F). Components (A) to (F) are described in detail below.

[0180] <(A)Component>

[0181] The component (A) is an organopolysiloxane having two or more alkenyl groups. The thermally conductive composition contains the component (A), and thus can form a cured product having a moderate hardness by an addition reaction with the organohydrogenpolysiloxane described later. The organopolysiloxane having two or more alkenyl groups used as the component (A) may be linear or branched, or a mixture of linear and branched, but is preferably linear.

[0182] The alkenyl group in the component (A) may be contained at either the terminal or the middle of the molecular chain of the polysiloxane structure of the component (A), or may be contained at both the terminal and the middle. However, it is preferably contained at least at the terminal, more preferably contained at both terminals of the molecular chain composed of the polysiloxane structure, and further preferably contained only at both terminals.

[0183] As alkenyl, there is no particular limitation, and examples thereof include alkenyl having 2 to 8 carbon atoms, such as vinyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, etc. Among them, vinyl is preferred from the viewpoint of ease of synthesis, reactivity, etc. In addition, alkenyl is preferably an alkenyl directly bonded to a silicon atom.

[0184] The number of alkenyl groups in one molecule of the component (A) is not particularly limited as long as it is 2 or more, and is, for example, 2 to 4, preferably 2 to 3, and more preferably 2.

[0185] As the remaining groups bonded to the silicon atom other than the alkenyl group, alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, dodecyl, aryl groups such as phenyl, aralkyl groups such as 2-phenylethyl, 2-phenylpropyl, and further substituted hydrocarbon groups such as chloromethyl and 3,3,3-trifluoropropyl are also given as specific examples. Among them, methyl is preferred from the viewpoint of ease of synthesis. In addition, it is preferred that 80 mol% or more of the remaining groups bonded to the silicon atom are methyl, more preferably 90 mol% or more are methyl, and further preferably 100 mol% are methyl. It should be noted that component (A) does not have a hydrogen atom as the remaining group bonded to the silicon atom, that is, it is better that component (A) does not contain a hydrosilyl group.

[0186] (A) The organopolysiloxane of the component may be used alone or in combination of two or more.

[0187] The viscosity of the component (A) at 25° C. is not particularly limited, and is, for example, 80 to 5000 mPa·s, preferably 150 to 2500 mPa·s, more preferably 200 to 1500 mPa·s, and further preferably 250 to 800 mPa·s.

[0188] In addition, component (A) is sometimes mixed as a mixture with component (C) described later, and the viscosity of the mixture of component (A) and component (C) at 25°C is, for example, 80 to 5000 mPa·s, preferably 150 to 2500 mPa·s, more preferably 200 to 1500 mPa·s, and further preferably 250 to 800 mPa·s.

[0189] By making the viscosity of component (A) or the mixture of components (A) and (C) to be above the above lower limit, the crosslinking density in the cured product is prevented from being too high, and the flexibility after curing is easily maintained. In addition, by making it below the above upper limit, the thermally conductive composition can be prevented from becoming highly viscous. Furthermore, by making the viscosity within the above range, the reactivity of component (A) or components (A) and (C) can be easily made appropriate.

[0190] It should be noted that in the two-component thermally conductive composition, regarding the component (A), the viscosity at 25°C of the component (A) mixed in the first agent can be adjusted to the above viscosity range, and the viscosity at 25°C of the mixture of the component (A) and the component (C) mixed in the second agent can be adjusted to the above viscosity range.

[0191] The content of the component (A) is not particularly limited as long as it is appropriately selected so that the Raman intensity ratio H / Vi, the content ratio H / Vi, the total Vi content, the ratio of the DVi content to the total Vi content, etc. described below can be adjusted within a desired range. However, it is, for example, 20 to 70% by mass, preferably 25 to 60% by mass, and more preferably 30 to 50% by mass, relative to the total amount of the organopolysiloxane contained in the thermally conductive composition.

[0192] <(B) Ingredient>

[0193] The component (B) is an organohydrogen polysiloxane having two hydrosilyl groups. The thermally conductive composition contains the component (B), so that the component (B) reacts with the components (A) and (D) to form a cured product with appropriate hardness. In addition, the thermally conductive composition of the present invention contains not only the component (C) described later but also the component (B) as an organohydrogen polysiloxane, so that the crosslinking points do not become too dense, and a cured product with appropriate softness can be formed.

[0194] The component (B) may be linear or branched, or a mixture of linear and branched, but is preferably linear. In the component (B), the hydrosilyl group may be contained at the end of the molecular chain of the polysiloxane structure, or in the middle of the molecular chain, or may be contained at both the end and the middle, but is preferably contained at least at the end, and more preferably two hydrosilyl groups are contained at each of the two ends of the molecular chain of the polysiloxane structure.

[0195] In the (B) component, as the remaining groups bonded to the silicon atom other than the hydrosilyl group, alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, dodecyl, aryl groups such as phenyl, aralkyl groups such as 2-phenylethyl, 2-phenylpropyl, and further substituted hydrocarbon groups such as chloromethyl and 3,3,3-trifluoropropyl are also given as specific examples. Among them, methyl is preferred from the viewpoint of ease of synthesis. In addition, it is preferred that 80 mol% or more of the remaining groups bonded to the silicon atom are methyl, more preferably 90 mol% or more are methyl, and further preferably 100 mol% are methyl. It should be noted that the (B) component does not have an alkenyl group as the remaining group bonded to the silicon atom, that is, it is better that the (B) component does not contain an alkenyl group.

[0196] (B) The organopolysiloxane of the component may be used alone or in combination of two or more.

[0197] The viscosity of the component (B) at 25°C is not particularly limited, and is, for example, 10 to 2000 mPa·s, preferably 40 to 1500 mPa·s, and more preferably 80 to 1200 mPa·s. By making the viscosity of the component (B) above the above lower limit, the crosslinking density is prevented from becoming high, and the flexibility after curing is easily improved. In addition, the reactivity is prevented from becoming too fast, and the addition reaction is easily carried out appropriately. In addition, by making the viscosity of the component (B) below the upper limit, the reactivity can be prevented from decreasing or the thermally conductive composition can be prevented from becoming high-viscosity.

[0198] The content of component (B) is not particularly limited as long as it is appropriately selected so as to adjust the Raman intensity ratio p2 / p1, Raman intensity ratio H / Vi, b / (b+c), content ratio H / Vi, etc. described below to within a prescribed range. It is, for example, 3 to 35% by mass, preferably 5 to 30% by mass, and more preferably 8 to 25% by mass.

[0199] <(C) Ingredients>

[0200] The component (C) is an organohydrogenpolysiloxane having three or more hydrosilyl groups. The component (C) can cure the thermally conductive composition by addition reaction with the components (A) and (D), and form a crosslinked structure in the cured product.

[0201] The component (C) may be linear or branched, or a mixture of linear and branched, but is preferably linear. In the component (C), the hydrosilyl group may be contained at either the end of the molecular chain of the polysiloxane structure or in the middle of the molecular chain, but is preferably contained at both the end and in the middle.

[0202] The number of the hydrosilyl groups in one molecule of the component (C) is not particularly limited as long as it is 3 or more, and is, for example, 3 to 25, and preferably 8 to 20.

[0203] In the component (C), the remaining groups bonded to the silicon atom are the same as those listed in the component (B), but methyl groups are preferred from the viewpoint of ease of synthesis. In addition, preferably, 80 mol% or more of the remaining groups bonded to the silicon atom are methyl groups, more preferably 90 mol% or more are methyl groups, and further preferably 100 mol% are methyl groups. It should be noted that the component (C) does not have an alkenyl group as the remaining group bonded to the silicon atom, that is, it is preferred that the component (C) does not contain an alkenyl group.

[0204] (C) The organopolysiloxane of the component may be used alone or in combination of two or more.

[0205] The content of component (C) is not particularly limited as long as it is appropriately selected so as to adjust the Raman intensity ratio p2 / p1, Raman intensity ratio H / Vi, b / (b+c), content ratio H / Vi, etc. described below to within a prescribed range. It is, for example, 0.2 to 8% by mass, preferably 0.4 to 5% by mass, and more preferably 0.7 to 3% by mass.

[0206] <(D) Ingredient>

[0207] Component (D) is an organopolysiloxane having one alkenyl group or methacryloyl group. The thermally conductive composition contains component (D), thereby preventing the crosslinking points from becoming too dense, and even when used in an environment above 150°C, the flexibility of the cured product can be well maintained, thereby improving reliability. Therefore, even if the cured product of the thermally conductive composition is used as a heat dissipation gap filler or the like in an environment above 150°C, it is possible to suppress peeling relative to a heating element, a heat sink, etc., and suppress the increase in thermal resistance. Furthermore, by increasing the flexibility after curing, for example, when the composition is made thick, it can exhibit cushioning properties and can be suitably used in a vibrating environment. In addition, since component (D) undergoes an addition reaction with component (B) or (C) during curing, it can also prevent seepage after curing.

[0208] The organopolysiloxane used as the component (D) may be linear or branched, or may be a mixture of a linear and branched organopolysiloxane, but is preferably linear.

[0209] The alkenyl group or the methacryloyl group may be contained at the end of the molecular chain of the polysiloxane structure or in the middle of the molecular chain, but is preferably contained at the end, and more preferably contained at one end of the molecular chain of the polysiloxane structure. It is preferred that the component (D) contains one alkenyl group or one methacryloyl group in the molecule, but preferably contains one methacryloyl group from the viewpoint of obtaining a cured product with excellent heat resistance.

[0210] The alkenyl group in the component (D) is not particularly limited, and examples thereof include alkenyl groups having 2 to 8 carbon atoms, and specific examples thereof are as described in the component (A), and vinyl groups are preferred from the viewpoint of ease of synthesis, etc. In addition, the alkenyl group is preferably an alkenyl group directly bonded to a silicon atom.

[0211] On the other hand, the methacryloyl group may be a methacryloyl group directly bonded to the silicon atom, but may also be bonded to the silicon atom via any divalent group (for example, a divalent saturated aliphatic hydrocarbon group, a group represented by -XO- (wherein X is a divalent saturated aliphatic hydrocarbon group)) or an oxygen atom.

[0212] In the component (D), the remaining groups bonded to the silicon atom are the same as those listed in the component (A), but methyl groups are preferred from the viewpoint of ease of synthesis. In addition, preferably, 80 mol% or more of the remaining groups bonded to the silicon atom are methyl groups, more preferably 90 mol% or more are methyl groups, and further preferably 100 mol% are methyl groups. It should be noted that the component (D) does not have a hydrogen atom as the remaining group bonded to the silicon atom, that is, the component (D) preferably does not contain a hydrosilyl group.

[0213] (D) The organopolysiloxane of the component may be used alone or in combination of two or more.

[0214] The viscosity of the component (D) at 25° C. is not particularly limited, and is, for example, 10 to 2000 mPa·s, preferably 50 to 1000 mPa·s, and more preferably 80 to 600 mPa·s.

[0215] By making the viscosity of component (D) above the above lower limit, it is easy to reduce the crosslinking density in the cured product and to improve the softness after curing. In addition, by being below the above upper limit, it is possible to prevent the thermally conductive composition from becoming highly viscous. In addition, by adjusting the viscosity of component (D) to within the above range, the reactivity of component (D) can be adjusted to be moderate.

[0216] The content of the component (D) is not particularly limited as long as it is appropriately selected so that the Raman intensity ratio H / Vi, the content ratio H / Vi, the total Vi content, the ratio of the DVi content to the total Vi content, etc. described below can be adjusted within a desired range. However, it is, for example, 1 to 30% by mass, preferably 5 to 25% by mass, and more preferably 8 to 20% by mass, relative to the total amount of the organopolysiloxane contained in the thermally conductive composition.

[0217] <(E) Ingredient>

[0218] (E) Component is a thermally conductive filler. The thermally conductive composition of the present invention contains a thermally conductive filler, thereby improving the thermal conductivity of the thermally conductive composition and a cured product (thermally conductive member) obtained by curing the thermally conductive composition.

[0219] Examples of the thermally conductive filler include metals, metal oxides, metal nitrides, metal hydroxides, carbon materials, oxides other than metals, nitrides, carbides, etc. Examples of the shape of the thermally conductive filler include spherical shapes and irregular powders.

[0220] Among the thermally conductive filling materials, as metals, aluminum, copper, nickel, etc. can be cited. As metal oxides, aluminum oxide represented by aluminum oxide, magnesium oxide, zinc oxide, etc. can be cited. As metal nitrides, aluminum nitride, etc. can be exemplified. As metal hydroxides, aluminum hydroxide can be cited. Further, as carbon materials, spherical graphite, diamond, etc. can be cited. As oxides, nitrides, and carbides other than metals, quartz, boron nitride, silicon carbide, etc. can be cited. Among them, as thermally conductive filling materials, from the viewpoint of improving thermal conductivity, metal oxides, metal nitrides, and carbon materials are preferred, and metal oxides are more preferred among them. In addition, specifically, aluminum oxide, aluminum nitride, and diamond are preferred, and aluminum oxide is further preferred.

[0221] These thermally conductive fillers may be used alone or in combination of two or more. For example, from the viewpoint of improving thermal conductivity, it is preferred to use at least one of diamond and aluminum nitride together with aluminum oxide. In addition, from the viewpoint of balancing thermal conductivity and flame retardancy, it is preferred to use aluminum oxide together with aluminum hydroxide.

[0222] The average particle size of the thermally conductive filler is preferably 0.1 to 200 μm, more preferably 0.3 to 100 μm, and even more preferably 0.5 to 70 μm.

[0223] The thermally conductive filler preferably uses a small-particle thermally conductive filler having an average particle size of 0.1 μm or more and 5 μm or less, and a large-particle thermally conductive filler having an average particle size of more than 5 μm and 200 μm or less. The filling rate can be increased by using thermally conductive fillers having different average particle sizes. It should be noted that the average particle size refers to the particle size (D50) when the volume accumulation is 50% in the particle size distribution of the thermally conductive filler obtained by the laser diffraction / scattering method.

[0224] The content of the thermally conductive filler in the thermally conductive composition is preferably 150 to 4000 parts by mass, more preferably 500 to 3500 parts by mass, further preferably 1000 to 3200 parts by mass, and further preferably 1500 to 3000 parts by mass, based on 100 parts by mass of the organopolysiloxane contained in the thermally conductive composition.

[0225] Furthermore, when the total amount of the thermally conductive composition is 100 volume %, the volume-based content of the thermally conductive filler is preferably 50 to 95 volume %, more preferably 70 to 93 volume %, further preferably 75 to 92 volume %, and further preferably 80 to 90 volume %.

[0226] By making the content of the thermally conductive filler material greater than or equal to the above lower limit, a certain thermal conductivity can be imparted to the thermally conductive composition and its cured product. By making the content of the thermally conductive filler material less than or equal to the above upper limit, the thermally conductive filler material can be appropriately dispersed. In addition, the viscosity of the thermally conductive composition can also be prevented from becoming excessively high.

[0227] <(F)Component>

[0228] (F) Component is a platinum-based curing catalyst. The thermally conductive composition of the present invention contains a platinum-based curing catalyst, which can promote the addition reaction of the organopolysiloxane containing alkenyl groups and the organohydrogenpolysiloxane, so that the thermally conductive composition is properly cured. There are no particular limitations on the platinum-based curing catalyst, and examples include chloroplatinic acid, coordination compounds of chloroplatinic acid and olefins, vinyl siloxanes or acetylene compounds, etc. The content of the platinum-based curing catalyst in the thermally conductive composition is not particularly limited as long as it contains an amount that can promote the addition reaction, and is, for example, 0.001 to 1 part by mass, preferably 0.005 to 0.5 parts by mass, relative to 100 parts by mass of the organopolysiloxane contained in the thermally conductive composition.

[0229] <(G) Ingredients>

[0230] The thermally conductive composition of the present invention preferably further contains an organopolysiloxane having no addition reaction group as component (G). The thermally conductive composition of the present invention contains component (G), so that in the cured product, more than a certain amount of components are not incorporated into the cross-linked structure, which is easy to improve flexibility. In addition, it is easy to reduce the viscosity of the thermally conductive composition and improve operability. It should be noted that the addition reaction group refers to a functional group that reacts by an addition reaction, and representative examples include alkenyl, methacryloyl, acryloyl, hydrosilyl, etc. In addition, by including component (G), the cured product can be made soft.

[0231] As component (G), there can be mentioned (G-1) silicone oil and (G-2) organopolysiloxane having at least one alkoxy group. Component (G) only needs to contain any one of component (G-1) and component (G-2), but preferably contains at least component (G-2). By containing component (G-2), the viscosity of the thermally conductive composition can be easily reduced. When the thermally conductive composition contains component (G-2), it can further contain component (G-1).

[0232] As (G-1) silicone oil, in addition to straight-chain silicone oils such as dimethyl silicone oil and phenylmethyl silicone oil, non-reactive modified silicone oils, etc., in which non-reactive organic groups are introduced into the main chain having a polysiloxane structure, the side chain combined with the main chain, or the end of the main chain. The so-called non-reactive organic group is an organic group that does not have an addition reaction group. As non-reactive modified silicone oils, for example, polyether-modified silicone oils, aralkyl-modified silicone oils, fluoroalkyl-modified silicone oils, long-chain alkyl-modified silicone oils, higher fatty acid ester-modified silicone oils, higher fatty acid amide-modified silicone oils, and phenyl-modified silicone oils can be cited. Among the above, as silicone oil, straight-chain silicone oils are preferred, and among the straight-chain silicone oils, dimethyl silicone oil is more preferred.

[0233] (G-1) The silicone oil may be used alone or in combination of two or more.

[0234] The component (G-2) may be linear or branched, or a mixture of linear and branched, but is preferably linear. In addition, the component (G-2) may be an organopolysiloxane having at least one alkoxy group, but preferably an organopolysiloxane having at least one alkoxy group at the molecular chain end of the polysiloxane structure, and more preferably an organopolysiloxane having at least one alkoxy group only at one end. It is presumed that the component (G-2) has an alkoxy group, especially an alkoxy group at the end, so that it is easy to react or interact with functional groups present on the surface of the thermally conductive filler material, and combined with the polysiloxane structure, the friction of the filler material is reduced, and the viscosity of the thermally conductive composition is easily reduced.

[0235] Specifically, the component (G-2) preferably has a structure represented by the following formula (X).

[0236]

[0237] (In formula (X), R 1 , R 2 , R 4 , R 5 are each independently a saturated hydrocarbon group, R 3 is an oxygen atom or a divalent hydrocarbon group, n is an integer of 15 to 315, and m is an integer of 0 to 2)

[0238] By using the component (G-2) having a structure represented by the formula (X), the viscosity reducing effect of the thermally conductive composition is further improved.

[0239] In formula (X), R 1 , R 2 , R 4 , R 5 Each independently represents a saturated hydrocarbon group. Examples of the saturated hydrocarbon group include alkyl groups such as linear alkyl groups, branched alkyl groups, and cyclic alkyl groups, aryl groups, aralkyl groups, and halogenated alkyl groups.

[0240] Examples of the linear alkyl group include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, eicosyl, etc. Examples of the branched alkyl group include isopropyl, tert-butyl, isobutyl, 2-methylundecyl, 1-hexylheptyl, etc. Examples of the cyclic alkyl group include cyclopentyl, cyclohexyl, cyclododecyl, etc.

[0241] Examples of the aryl group include phenyl, tolyl, xylyl, etc. Examples of the aralkyl group include benzyl, phenethyl, 2-(2,4,6-trimethylphenyl)propyl, etc. Examples of the halogenated alkyl group include 3,3,3-trifluoropropyl, 3-chloropropyl, etc.

[0242] From the viewpoint of improving the viscosity reducing effect, R in formula (X) 1 ~R 5 , m, and n are preferably as follows.

[0243] R in formula (X) 1 An alkyl group having 1 to 8 carbon atoms is preferred, an alkyl group having 2 to 6 carbon atoms is more preferred, and a butyl group is particularly preferred.

[0244] R in formula (X) 2 , R 4 , R 5 Each independently is preferably an alkyl group having 1 to 8 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and particularly preferably a methyl group.

[0245] R in formula (X) 3 is an oxygen atom or a divalent hydrocarbon group, preferably a divalent hydrocarbon group. Examples of the divalent hydrocarbon group include a methylene group, an ethylene group, a propylene group, a butylene group, and a methylethylene group, among which an ethylene group is preferred.

[0246] n in formula (X) is an integer of 15 to 315, preferably an integer of 18 to 280, and more preferably an integer of 20 to 220. m in formula (X) is an integer of 0 to 2, preferably 0 or 1, and more preferably 0. Therefore, the component (G-2) is preferably an organopolysiloxane having a trialkoxysilyl group at one end.

[0247] The component (G-2) may be used alone or in combination of two or more.

[0248] The viscosity of the component (G) at 25°C is not particularly limited, and is, for example, 1 to 800 mPa·s, preferably 5 to 250 mPa·s, and more preferably 10 to 150 mPa·s. By setting the viscosity of the component (G) within the above range, the viscosity of the thermally conductive composition is effectively reduced by the component (G), and a cured product is easily formed.

[0249] The content of component (G) in the thermally conductive composition is based on the total amount of the organopolysiloxane contained in the thermally conductive composition, for example, 3 to 63% by mass. By making the content of component (G) above the above lower limit, it is easy to improve the softness of the cured product obtained from the thermally conductive composition, and it is also easy to reduce the viscosity of the thermally conductive composition by component (G). In addition, by making the content of component (G) below the above upper limit, a certain curability can be imparted to the thermally conductive composition, it is easy to obtain a cured product with desired physical properties, and it is also easy to prevent exudation after curing. The content of component (G) in the thermally conductive composition is preferably 5 to 50% by mass, more preferably 10 to 40% by mass, and further preferably 15 to 35% by mass.

[0250] As described above, the component (G) preferably contains the component (G-2). The content of the component (G-2) in the thermally conductive composition is preferably 2 to 40% by mass, more preferably 4 to 30% by mass, and even more preferably 8 to 20% by mass, based on the total amount of the organopolysiloxane contained in the thermally conductive composition. By containing the component (G-2) in a certain amount or more in the component (G), the viscosity of the thermally conductive composition can be easily reduced.

[0251] In the thermally conductive composition of the present invention, the total content of the components (A) to (D) and (G) is preferably 2 to 40% by mass relative to the total amount of the thermally conductive composition. By making the total amount of the components (A) to (D) and (G) greater than a certain amount, these components can appropriately function as a binder resin, and the thermally conductive filler can be appropriately retained by these components. In addition, by making the above total content less than a certain amount, a large amount of thermally conductive filler can be contained.

[0252] The total content of the components (A) to (D) and (G) is more preferably 3 to 20% by mass, further preferably 3.5 to 15% by mass, and further preferably 4 to 10% by mass, based on the total amount of the thermally conductive composition.

[0253] The organopolysiloxane in the thermally conductive composition of the present invention may be composed of components (A) to (D) or components (A) to (D) and component (G), but may contain organopolysiloxanes other than components (A) to (D) and component (G) within a range that does not impair the effects of the present invention. The content of the organopolysiloxane other than components (A) to (D) and component (G) is, for example, 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and most preferably 0% by mass, relative to the total amount of the organopolysiloxane contained in the thermally conductive composition.

[0254] The thermally conductive composition of the present invention may contain various additives. Examples of additives include reaction control agents, dispersants, flame retardants, plasticizers, antioxidants, colorants, and the like. It should be noted that each additive may be contained in either the first component or the second component of the two-component thermally conductive composition, but may also be contained in both. As the additive, one or more additives may be appropriately selected from these and used.

[0255] <Raman intensity ratio p2 / p1>

[0256] In one embodiment of the present invention, the thermally conductive composition has a Raman spectrum at 2160 cm -1 The Raman intensity at p1 and 2130 cm -1 The Raman intensity p2 at satisfies the following relationship (1-1).

[0257] p2 / p1>3.00 (1-1)

[0258] 2160cm in Raman spectra -1 The Raman intensity p1 at 2130 cm in the Raman spectrum is the Raman intensity at the peak wavelength derived from the hydrosilyl group contained in the middle of the molecular chain of the polysiloxane structure. -1 The Raman intensity p2 at is the Raman intensity of the peak wavelength derived from the hydrosilyl groups contained at the ends of the molecular chains of the polysiloxane structure. Therefore, p2 / p1 can be considered as an index representing the amount of the terminal hydrosilyl groups relative to the amount of the hydrosilyl groups contained in the middle of the molecular chain.

[0259] By making p2 / p1 greater than 3.0, the amount of hydrosilyl groups contained at the ends of the molecular chain increases, while the amount of hydrosilyl groups contained in the middle of the molecular chain decreases, and the crosslinking points tend to become sparse, and the softness of the cured product is also easily maintained in an environment above 150°C. Therefore, if the cured product of the thermally conductive composition is used as a heat dissipation gap filler in an environment above 150°C, it is not easy to peel off from the heating element, the heat dissipator, etc., and the unfavorable condition of increased thermal resistance is not easy to occur, and the reliability is improved. Furthermore, by increasing the softness, for example, when it is made thick, it can exert cushioning properties and can be used appropriately in an environment where vibration occurs.

[0260] From the viewpoint of making cross-linking points sparse and improving reliability and flexibility, p2 / p1 is preferably 3.10 or more, more preferably 3.20 or more, and even more preferably 3.30 or more.

[0261] In addition, p2 / p1 is preferably less than 5.5. By making p2 / p1 less than 5.5, it is easy to introduce a 3D crosslinked structure into the cured product with a moderate crosslinking density. Therefore, even if heated at high temperature for a long time, it is easy to maintain the hardness at a certain value, and it is easy to make long-term heat resistance and the like good. From the above viewpoints, p2 / p1 is more preferably less than 4.5, more preferably less than 4.2, and more preferably less than 4.0.

[0262] The value of the Raman intensity ratio p2 / p1 can be adjusted by adjusting the content of component (B), the concentration of the hydrosilyl groups at the ends of the molecular chain of component (B), the content of component (C), and the concentration of the hydrosilyl groups in the middle of the molecular chain of component (C). Specifically, the value of p2 / p1 can be increased by increasing the content of component (B), increasing the concentration of the hydrosilyl groups at the ends of the molecular chain contained in component (B), decreasing the content of component (C), and decreasing the concentration of the hydrosilyl groups in the middle of the molecular chain contained in component (C). In addition, the value of p2 / p1 can be decreased by the opposite adjustment.

[0263] <Raman intensity ratio H / Vi>

[0264] The ratio of the intensity of the peak derived from the hydrosilyl group to the intensity of the peak derived from the alkenyl group and the methacryloyl group in the Raman spectrum (also referred to as "Raman intensity ratio H / Vi") is, for example, 7.00 to 13.50, preferably 7.00 to 12.00, and more preferably 7.50 to 11.00. By making the Raman intensity ratio H / Vi within the above range, the number of the hydrosilyl group and the total number of the alkenyl group and the methacryloyl group are balanced, and it is easy to properly cure the components (A) to (D), for example, even at room temperature.

[0265] The value of the Raman intensity ratio H / Vi can be adjusted by adjusting the content of the component (A), the content of the component (B), the content of the component (C), the content of the component (D), the concentration of the alkenyl group, the methacryloyl group, and the hydrosilyl group of each component. Specifically, the value of H / Vi can be increased by reducing the content of the component (A), reducing the content of the component (D), reducing the concentration of the alkenyl group of the component (A), reducing the total concentration of the alkenyl group and the methacryloyl group of the component (D), increasing the content of the component (B), increasing the content of the component (C), increasing the concentration of the hydrosilyl group contained in the component (B), and increasing the concentration of the hydrosilyl group contained in the component (C). In addition, the value of H / Vi can be reduced by the opposite adjustment.

[0266] It should be noted that the measurement of the Raman spectroscopic spectrum is preferably performed by separating at least the organopolysiloxane and the thermally conductive filler from the thermally conductive composition, and performing Raman measurement on the organopolysiloxane. In this case, components other than the organopolysiloxane may be mixed in the organopolysiloxane as long as they do not affect the measurement. Therefore, generally, the liquid component and the solid component are separated by a centrifuge or the like, and the Raman spectroscopic spectrum of the liquid component is preferably measured.

[0267] In addition, for the two-component thermally conductive composition, the Raman intensity ratios p2 / p1 and H / Vi were calculated by Raman measurement for the first and second agents respectively, but the Raman intensity ratio p2 / p1 was calculated from the Raman spectroscopic spectrum of the second agent. This is because the organohydrogen polysiloxane is not contained in the first agent, but only in the second agent. The measurement conditions of the Raman measurement are as described in the examples. It should be noted that the alkenyl group is typically a vinyl group, and the above Raman intensity ratio H / Vi can be obtained by calculating the index of the hydrosilyl group / (vinyl group+methacryloyl group) ratio as shown in the examples described later.

[0268] In the present invention, “combining the first dose with the second dose” or “combining the second dose with the first dose” means calculating using the values ​​measured for the first dose and the second dose, respectively, as described above.

[0269] <Concentration ratio of hydrosilyl groups>

[0270] In the thermally conductive composition according to one embodiment of the present invention, the component (B) and the component (C) are contained so as to satisfy the relationship of the following formula (1-2).

[0271] b / (b+c)>0.45 (1-2)

[0272] In formula (1-2), b is the concentration of the hydrosilyl group possessed by component (B), and c is the concentration of the hydrosilyl group possessed by component (C). It should be noted that the concentration of the hydrosilyl group here refers to the concentration of the hydrosilyl group in the thermally conductive composition. However, in the two-component thermally conductive composition described later, the organohydrogenpolysiloxane is not included in the first agent, but only in the second agent. Therefore, in the two-component thermally conductive composition, it can also be said to refer to the concentration of the hydrosilyl group in the second agent. That is, it is better that the components (B) and (C) are included in the second agent in a manner that satisfies the relationship of formula (1-2).

[0273] The above-mentioned concentration ratio of the hydrosilyl group can be adjusted by adjusting the content of the component (B), the concentration of the hydrosilyl group of the component (B), the content of the component (C), and the concentration of the hydrosilyl group of the component (C). Specifically, the concentration ratio of the hydrosilyl group can be increased by increasing the content of the component (B), increasing the concentration of the hydrosilyl group contained in the component (B), decreasing the content of the component (C), or decreasing the concentration of the hydrosilyl group contained in the component (C), or by any one or a combination thereof. In addition, the concentration ratio of the hydrosilyl group can be decreased by the opposite adjustment.

[0274] In the present composition, if b / (b+c) is greater than 0.45, the crosslinking points tend to become sparse, and the softness of the cured product tends to be well maintained in an environment of 150°C or above. Therefore, if the cured product of the thermally conductive composition is used as a heat dissipation gap filler in an environment of 150°C or above, it is less likely to peel off from the heating element, the heat dissipation element, etc., and the unfavorable condition of increased thermal resistance is less likely to occur, and reliability is improved. Furthermore, by increasing the softness, for example, when the thickness is made, the cushioning property can be exerted, and it can be suitably used in an environment where vibration occurs.

[0275] From the viewpoint of making the cross-linking points sparse and improving reliability and flexibility, b / (b+c) is preferably 0.48 or more, more preferably 0.50 or more, and even more preferably 0.52 or more.

[0276] b / (b+c) is preferably less than 0.85. By making b / (b+c) less than 0.85, it is easy to introduce a cross-linked structure into the cured product with a moderate cross-linking density. Therefore, even if heated at high temperature for a long time, it is easy to maintain the hardness at a certain value, and it is easy to make long-term heat resistance and the like good. From the above viewpoints, b / (b+c) is more preferably less than 0.75, more preferably less than 0.70, and more preferably less than 0.63.

[0277] In the present invention, any one of the requirements of the above formula (1-1) and the requirements of the formula (1-2) may be satisfied, but both of them may be satisfied.

[0278] The concentrations of the hydrosilyl groups of the components (B) and (C) may be values ​​calculated from the integration ratio of the 1H-NMR spectrum measured using an NMR measuring apparatus.

[0279] <Alkenyl and Methacryloyl Content>

[0280] The total content of alkenyl and methacryloyl groups in the thermally conductive composition (hereinafter also referred to as "total Vi content") is preferably 5.0 μmol / g or less. By making the total Vi content 5.0 μmol / g or less, the crosslinking density in the cured product is low, and the flexibility is easily improved. The total Vi content is more preferably 4.8 μmol / g or less, further preferably 4.5 μmol / g or less, and further preferably 4.2 μmol / g or less.

[0281] From the viewpoint of imparting certain curability and appropriate crosslinking density to the thermal conductive composition, the total Vi content is preferably 0.5 μmol / g or more, more preferably 1.0 μmol / g or more, further preferably 2.0 μmol / g or more, and further preferably 3.0 μmol / g or more.

[0282] The alkenyl group content may be a value calculated from an integrated ratio of a 1H-NMR spectrum measured using an NMR measuring apparatus.

[0283] In addition, the total content of alkenyl and methacryloyl groups contained in the (D) component (i.e., an organopolysiloxane having one alkenyl or methacryloyl group) (hereinafter also referred to as "DVi content") is preferably 0.05 or more relative to the above-mentioned total Vi content. By making the amount of alkenyl and methacryloyl groups in the (D) component more than a certain amount, the cross-linking points are prevented from becoming too dense, and the flexibility and reliability are easily improved. The DVi content is more preferably 0.10 or more relative to the total Vi content, further preferably 0.15 or more, and further preferably 0.19 or more. In addition, from the viewpoint of imparting a certain curability and a moderate cross-linking density to the cured product, the DVi content is preferably 0.40 or less relative to the total Vi content, more preferably 0.35 or less, further preferably 0.30 or less, and further preferably 0.28 or less.

[0284] It should be noted that the total content of the alkenyl group and the methacryloyl group can be adjusted by adjusting the content of the component (A), the content of the component (D), the concentration of the alkenyl group of the component (A), and the concentration of the alkenyl group and the methacryloyl group of the component (D). Specifically, the total content of the alkenyl group and the methacryloyl group can be increased by increasing the content of the component (A), increasing the content of the component (D), increasing the concentration of the alkenyl group of the component (A), and increasing the total concentration of the alkenyl group and the methacryloyl group of the component (D). In addition, the total content of the alkenyl group and the methacryloyl group can be reduced by adjusting the opposite.

[0285] In addition, the total content of alkenyl and methacryloyl groups contained in the component (D) can be adjusted by adjusting the content of the component (D) and the concentration of alkenyl and methacryloyl groups in the component (D). Specifically, the total content of alkenyl and methacryloyl groups contained in the component (D) can be increased by either or in combination of increasing the content of the component (D) or increasing the total concentration of alkenyl and methacryloyl groups in the component (D). In addition, the total content of alkenyl and methacryloyl groups contained in the component (D) can be decreased by adjusting the opposite.

[0286] <Content ratio H / Vi>

[0287] The content H of the hydrosilyl group and the total content Vi of the alkenyl group and the methacryloyl group in the thermally conductive composition preferably satisfy the relationship of the following formula (4).

[0288] 0.85≤H / Vi≤1.1 (4)

[0289] By satisfying the relationship of the above formula (4), the curability of the thermally conductive composition can be improved, for example, the thermally conductive composition can be appropriately cured even at room temperature. From the viewpoint of curability, H / Vi is more preferably 0.90 to 1.05, and even more preferably 0.95 to 1.03.

[0290] The above-described hydrosilyl group concentration ratio (b / (b+c)), total Vi content, DVi content, and content ratio H / Vi can be calculated from the functional group amount of each component to be blended and the content of each component.

[0291] It should be noted that the method for adjusting the value of the above-mentioned content ratio H / Vi is the same as the method for adjusting the Raman intensity ratio H / Vi.

[0292] <E type hardness>

[0293] The thermally conductive composition of the present invention, after being left at 25° C. for 24 hours and further left at 150° C. for 250 hours, has an E-type hardness (E2) that satisfies the following formula (2).

[0294] E2<70 (2)

[0295] In addition, when the thermally conductive composition is a two-component type thermally conductive composition, the first component and the second component are mixed and then left to stand at 25° C. for 24 hours. The same applies to the measurement of other hardnesses.

[0296] If the E-type hardness (E2) is 70 or more, it is easy to maintain the softness of the cured product in an environment of 150°C or more, but it is difficult to relieve the stress of vibration and the like due to being too hard, so it is easy to peel off from the heating element or the heat sink. Therefore, if the cured product of the thermally conductive composition is used as a heat dissipation gap filler (thermal conductive component) in an environment of 150°C or more, peeling relative to the heating element or the heat sink occurs, the unfavorable condition of increased thermal resistance occurs, and reliability is reduced. From the viewpoint of softness and reliability, the E-type hardness (E2) is preferably 69 or less, more preferably 67 or less, and further preferably 64 or less. It should be noted that if the softness becomes higher, it is easy to exert cushioning properties, and it can be suitably used in an environment where vibration occurs.

[0297] In addition, the E-type hardness (E2) is not particularly limited, and is, for example, 30 or more, preferably 40 or more, and more preferably 50 or more. By making the E-type hardness (E2) be a certain value or more, the softness of the cured product can be easily maintained in an environment of 150° C. or more, and further, for example, the weight of a member disposed on the upper portion of the cured product can be fully supported, and the cured product can be prevented from being excessively compressed in the thickness direction during use.

[0298] The above-mentioned E-type hardness (E2) can be adjusted by, for example, adjusting the concentration of each component, the concentration of the alkenyl group, methacryloyl group, and hydrosilyl group of each component, the Raman intensity ratio H / Vi, and the content ratio H / Vi. Specifically, E2 can be improved by increasing the content of component (A), increasing the content of component (C), increasing the concentration of the alkenyl group of component (A), increasing the concentration of the hydrosilyl group of component (C), and making the Raman intensity ratio H / Vi and the content ratio H / Vi in a more preferred range or a combination thereof. On the other hand, E2 can be lowered by increasing the content of component (B), increasing the content of component (D), adding more component (G) as needed, lowering the concentration of the alkenyl group, methacryloyl group, and hydrosilyl group of each component, and adjusting the Raman intensity ratio H / Vi and the content ratio H / Vi in a direction beyond the more preferred range.

[0299] The thermally conductive composition preferably has a type E hardness (E1) after being left at 25° C. for 24 hours and the relationship between the above-mentioned E2 satisfies the following formula (3).

[0300] 1.4≤E2 / E1≤3.5 (3)

[0301] When E2 / E1 is 1.4 or more, the film can have flexibility and predetermined heat resistance. When E2 / E1 is 3.5 or less, the hardness after curing does not change too much, so stable fixing can be achieved.

[0302] E2 / E1 is more preferably 1.8 or more and more preferably 3.0 or less.

[0303] The E-type hardness (E1) of the thermally conductive composition after being placed at 25°C for 24 hours is preferably 10 or more, more preferably 15 or more, and further preferably 20 or more. The thermally conductive composition makes the E-type hardness (E1) above a certain value, so that a cured product with a certain hardness can be obtained simply by placing it at room temperature. Therefore, for example, the weight of the component arranged on the upper part of the cured product can be fully supported in the state after being cured at room temperature, and compression in the thickness direction during use can be prevented. In addition, the E-type hardness (E1) of the thermally conductive composition is preferably 50 or less, more preferably 46 or less, and further preferably 40 or less. By making the E-type hardness (E1) below the above-mentioned upper limit value, the softness of the cured product of the thermally conductive composition can be improved.

[0304] In order to adjust the relationship between the above-mentioned E-type hardness (E1) and the above-mentioned E2 to a specified range, for example, the Raman intensity ratio p2 / p1 or the Raman intensity ratio H / Vi is adjusted to a specified range, and a specified amount of the (F) component is added in a manner that the curing reaction does not become too slow.

[0305] If the E-type hardness after being placed at 25°C for 24 hours and further placed at 150°C for 1000 hours is set to E3, the hardness change shown by the value of E3-E2 indicates the hardness change when heated at 150°C for a long time. The lower the value of E3-E2, the less the performance change even for long-term use at a temperature above 150°C, and the good long-term heat resistance. From the viewpoint of long-term heat resistance, the hardness change shown by the value of E3-E2 is preferably less than 6, more preferably less than 4, and preferably less than 2. It should be noted that the hardness change shown by the value of E3-E2 is not particularly limited, but is usually greater than 0.

[0306] [Two-component thermally conductive composition]

[0307] The thermally conductive composition of the present invention may be a one-component type or a two-component type in which the first agent and the second agent are combined, but the two-component type is preferred from the viewpoint of storage stability. The two-component type is a thermally conductive composition obtained by mixing the first agent and the second agent when used.

[0308] In the two-component thermally conductive composition, the mass ratio of the first agent to the second agent (second agent / first agent) is preferably 1 or a value close to 1, preferably 0.8 to 1.2, more preferably 0.9 to 1.1, and more preferably 0.95 to 1.05. Thus, by setting the mass ratio of the first agent to the second agent to 1 or a value close to 1, the preparation of the thermally conductive composition becomes easy.

[0309] In the two-component thermally conductive composition, the method for obtaining the thermally conductive composition by mixing the first agent and the second agent is not limited, and for example, a static mixer, a mixer having a stirring blade, a vibration mixer, a rotation and revolution mixer, etc. can be used.

[0310] In the two-component thermally conductive composition, the first agent contains an organopolysiloxane having an alkenyl group (an organopolysiloxane containing an alkenyl group) and (F) a platinum-based curing catalyst, but does not contain an organohydrogenpolysiloxane. In addition, the second agent contains an organohydrogenpolysiloxane, but does not contain (F) a platinum-based curing catalyst. Furthermore, at least one of the first agent and the second agent contains (E) a thermally conductive filler. In addition, it is preferred that both the first agent and the second agent contain (E) a thermally conductive filler.

[0311] More specifically, the first agent contains at least one of the components (A) and (D), and the component (F), but does not contain the component (B) and the above-mentioned component (C). On the other hand, the second agent contains the components (B) and (C), but does not contain the component (F). In addition, either the first agent or the second agent contains the component (E).

[0312] In addition, the first agent contains at least one of the components (A) and (D), the component (E), and the component (F), but does not contain the component (B) and the above-mentioned component (C). On the other hand, the second agent more preferably contains the components (B), (C), and (E), but does not contain the component (F).

[0313] The first agent having the above-mentioned structure contains (F) a platinum-group curing catalyst that accelerates the addition reaction, but does not contain an organohydrogenpolysiloxane, and thus can prevent the addition reaction from proceeding before mixing with the second agent. The second agent contains an organohydrogenpolysiloxane, but does not contain (F) a platinum-group curing catalyst that accelerates the addition reaction, and thus can prevent the addition reaction from proceeding before mixing with the first agent.

[0314] The alkenyl group-containing organopolysiloxane constituting the thermally conductive composition may be entirely contained in the first agent, but preferably a portion is contained in the first agent and the remainder is contained in the second agent. More specifically, the components (A) and (D) in the thermally conductive composition may be entirely contained in the first agent, but preferably a portion of the components (A) and (D) are contained in the first agent and the remainder of the components (A) and (D) are contained in the second agent.

[0315] In this way, by making the alkenyl-containing organopolysiloxane be contained in the first agent and the second agent separately, it is easy to adjust the viscosity of the first agent and the second agent to a desired range, and it is easy to make the mass ratio of the first agent to the second agent 1 or a value close to 1. It should be noted that the second agent also contains an organohydrogenpolysiloxane, but does not contain (F) a platinum-based curing catalyst, so even if it contains an alkenyl-containing organopolysiloxane, the addition reaction can be substantially prevented from proceeding during storage, etc. It should be noted that the second agent can also contain a reaction control agent to prevent the reaction from proceeding in the second agent.

[0316] When the alkenyl group-containing organopolysiloxane is contained in the second agent, it can be mixed with the second agent as a mixture with the organohydrogenpolysiloxane. For example, the component (A) can be mixed with the second agent as a mixture with the component (C).

[0317] The organohydrogenpolysiloxane constituting the thermally conductive composition is entirely contained in the second agent and is not contained in the first agent.

[0318] The (E) thermally conductive filler material only needs to be included in any one of the first agent and the second agent for forming the thermally conductive composition, but is preferably included in both the first agent and the second agent as described above, and is more preferably contained approximately equally. Specifically, the ratio (mass ratio) of the content of the (E) thermally conductive filler material in the second agent to the content of the (E) thermally conductive filler material in the first agent is preferably 0.67 to 1.5, more preferably 0.83 to 1.2, and further preferably 0.91 to 1.1. By distributing the (E) thermally conductive filler material approximately equally to the first agent and the second agent, it is easy to reduce the viscosity difference between the first agent and the second agent, and it is also easy to make the mass ratio of the first agent to the second agent close to 1.

[0319] The thermally conductive composition preferably contains component (G), and component (G) is preferably included in at least one of the first agent and the second agent. However, component (G) is preferably included in at least the first agent, and more preferably included in both the first agent and the second agent. If component (G) is included in both the first agent and the second agent, the viscosity of the first agent and the second agent can be adjusted by component (G), and both the first agent and the second agent can be made to have a lower viscosity. It should be noted that when component (G) contains component (G-2), it is more effective and preferred to include component (G-2) in both the first agent and the second agent.

[0320] <Viscosity>

[0321] The viscosity VB of the binder resin contained in the thermally conductive composition at 25°C is not particularly limited, and is preferably 50 to 800 mPa·s, more preferably 80 to 600 mPa·s, and further preferably 100 to 400 mPa·s. It should be noted that the so-called viscosity VB of the binder resin is the viscosity of the organopolysiloxane contained in the thermally conductive composition, which is usually the viscosity of the components (A) to (D) or the mixture of the components (A) to (D) and the component (G), but in the case of containing organopolysiloxanes other than these, it is the viscosity of the mixture further containing the organopolysiloxane. Regarding the viscosity VB1 and VB2 of the binder resin of the first and second agents described later, they are also the viscosity of the organopolysiloxane contained in the first and second agents, respectively.

[0322] In the two-component thermally conductive composition, the viscosity VB1 and VB2 of the binder resin contained in the first and second components at 25° C. are preferably 50 to 800 mPa·s, more preferably 80 to 600 mPa·s, and even more preferably 100 to 400 mPa·s.

[0323] It should be noted that regarding the viscosity VB1 and VB2 of the binder resin in each of the first and second agents, it is preferable to mix the organopolysiloxanes contained in each of the first and second agents and measure the viscosity of the mixed organopolysiloxane. The viscosity VB of the binder resin in the thermally conductive composition can also be measured in the same manner, but in the case of a two-component thermally conductive composition, the approximate viscosity VB can also be estimated from the viscosity VB1 and VB2 of the binder resin in each of the first and second agents.

[0324] In the two-component thermally conductive composition, the viscosity V1 and V2 of the first and second agents at a temperature of 25° C. and a shear rate of 3.16 (1 / s) are preferably 10 to 1000 Pa·s, more preferably 50 to 700 Pa·s, and even more preferably 200 to 450 Pa·s. When the first and second agents have such viscosities, workability is easily improved.

[0325] Furthermore, the viscosity V of the thermally conductive composition of the present invention at a temperature of 25° C. and a shear rate of 3.16 (1 / s) is preferably 10 to 1000 Pa·s or less, more preferably 50 to 700 Pa·s or less, and even more preferably 200 to 450 Pa·s or less. The thermally conductive composition has such a viscosity that it has a predetermined fluidity before curing, and can be applied to narrow gaps and complex shapes.

[0326] In the case of a two-component type, the viscosity V of the thermally conductive composition can be determined by mixing the first and second components and measuring the mixture immediately. However, a rough value of the viscosity can also be estimated from the viscosities V1 and V2 of the first and second components.

[0327] From the viewpoint of making it easy to uniformly mix the thermally conductive composition, the difference (|V1-V2|) between the viscosity V1 of the first agent and the viscosity V2 of the second agent is preferably small. Specifically, the viscosity difference (|V1-V2|) between the first agent and the second agent is preferably 130 Pa·s or less, preferably 100 Pa·s or less, and more preferably 30 Pa·s or less. In addition, the viscosity difference (|V1-V2|) between the first agent and the second agent only needs to be 0 Pa·s or more.

[0328] [Thermal conductive member]

[0329] The thermally conductive composition of the present invention is preferably used as a thermally conductive member such as a heat dissipation gap filler. The thermally conductive member is a cured product obtained by curing the thermally conductive composition.

[0330] Thermally conductive components are used inside electronic devices, etc. Specifically, the thermally conductive component is interposed between a heating element and a heat sink, and conducts heat generated by the heating element to the heat sink, and dissipates heat from the heat sink. Here, various electronic components such as CPUs, power amplifiers, and power supplies used inside electronic devices can be cited as heating elements. In addition, heat sinks can be radiators, heat pumps, and metal housings of electronic devices.

[0331] In addition, the thermally conductive member is preferably used in, for example, electrical components. In the electrical components, the heat generating element is preferably arranged in the engine room, near the motor, etc. The present invention is particularly suitable for use in electrical components exposed to a high temperature environment of 150°C or higher. In addition, it is also suitable for heat dissipation of a heat generating element that generates heat at 150°C or higher.

[0332] The thermally conductive component is preferably formed by filling a thermally conductive composition in a gap between a heating element and a heat sink, for example, and curing the gap. Curing can be performed by heating, but is preferably performed near room temperature (for example, about 0 to 40°C, preferably about 15 to 35°C). By curing near room temperature, the thermally conductive component can be arranged inside an electronic device without applying a thermal history to the electronic components. In the case of a two-component thermally conductive composition, it is preferably cured by mixing the first agent and the second agent and then filling the gap between the heating element and the heat sink.

[0333] The shape of the thermally conductive member is not particularly limited, and it can be a sheet or other shapes. The thickness of the thermally conductive member is not particularly limited, and it can be, for example, 0.3 to 5 mm, preferably 0.5 to 4 mm. In the present invention, since the thermally conductive member is flexible, if the thickness is large (for example, 0.5 mm or more), the cushioning property can be exerted, and it can be suitably used in a vibrating environment.

[0334] Example

[0335] Hereinafter, the present invention will be described in further detail by way of examples, but the present invention is not limited to these examples at all.

[0336] [Raman measurement]

[0337] The first agent and the second agent were separated into liquid components and solid components (thermal conductive filler) using centrifugal separators, respectively. Raman spectra of the separated liquid components were measured. The Raman spectra were measured under the following conditions.

[0338] Equipment: inVia Raman microscope QONTOR manufactured by RENISHAW

[0339] Spectral range: 300~2500cm -1

[0340] Laser wavelength: 532nm, 100mW (dimming is 10%)

[0341] Grating: 1800 lines / mm

[0342] Irradiation time: 1.0s

[0343] Total: 100

[0344] Objective lens: 50 times

[0345] The Raman intensity ratio p2 / p1 is a Raman spectrum obtained from the second agent containing a hydrosilyl group, and is given by the wave number 2130 cm -1 Raman intensity p2 and wave number 2160cm -1 The Raman intensity p1 at is estimated.

[0346] The Raman intensity ratio H / Vi (the ratio of the intensity of the peak derived from the hydrosilyl group to the intensity of the peak derived from the alkenyl group and the methacryloyl group) was calculated as follows. That is, regarding the Raman spectra of the first agent and the Raman spectra of the second agent, first, the peak intensity at a wave number of 490 cm -1 The area of ​​the Si-O-Si peak at wave number 1600 cm -1 The area D of the peak of vinyl at wave number 1640 cm -1The peak area E of the methacryloyl group appearing at 2130-2160 cm -1 The area of ​​the peak of the hydrosilyl group that appeared is F. Next, the following calculation was performed based on the area C, and the error of the intensity in each measurement was corrected and standardized.

[0347] Area D / Area C = Area ratio D1

[0348] Area E / Area C = Area ratio E1

[0349] Area F / Area C=Area ratio F1

[0350] Next, the values ​​obtained by multiplying the area ratio D1, E1 of the first agent by the mass ratio of the liquid component contained in the first agent and the values ​​obtained by multiplying the area ratio D1, E1, F1 of the second agent by the mass ratio of the liquid component contained in the second agent were totaled to estimate D1, E1, F1 in the thermally conductive composition.

[0351] Furthermore, the index of the ratio of hydrosilyl group / (vinyl group+methacryloyl group) was calculated by the following formula: Since the vinyl group and the methacryloyl group have different Raman scattering intensities, the ratio was multiplied by 0.5 as a correction factor for calculation.

[0352] Raman intensity ratio H / Vi = area ratio F1 / [area ratio D+(area ratio E1×0.5)]

[0353] In addition, when the thermally conductive composition has an alkenyl group other than a vinyl group, the peak intensity derived from the alkenyl group other than a vinyl group is similarly calculated, and it is preferable to calculate the Raman intensity ratio H / Vi.

[0354] [Viscosity of Each Organopolysiloxane and Viscosity of Binder Resin]

[0355] The viscosity of each organopolysiloxane at 25° C. and the viscosities VB1 and VB2 of the binder resin contained in the first and second agents were measured as follows.

[0356] The rheometer "MCR-302e" manufactured by Antenna Pal was used, the temperature of the sample was adjusted to 25°C using a Peltier plate, and the viscosity was measured while continuously changing the shear rate in the range of 10 to 100 (1 / sec) using a cone plate of φ50 mm and an angle of 1°. Here, the viscosity value is the viscosity at a shear rate of 10 (1 / s).

[0357] [Viscosity of the first and second doses]

[0358] The viscosities V1 and V2 of the first and second agents were measured by the following method.

[0359] The rheometer "MCR-302e" manufactured by Antenna Pal was used, the sample temperature was adjusted to 25°C using a Peltier plate, and the viscosity was measured while continuously changing the shear rate in the range of 0.0001 to 100 (1 / s) using a φ25 mm parallel plate. The viscosities at shear rates of 0.0001 (1 / s), 3.16 (1 / s), and 6.31 (1 / s) are recorded in the table.

[0360] [Hardness of Cured Material of Thermally Conductive Composition]

[0361] The first agent and the second agent were filled in a 50cc 2-liquid parallel cylinder (1:1 mixing cylinder "CDA050-01-PP" manufactured by MIXPAC), and mixed using a static mixer (2-liquid mixing static mixer "MA6.3-12S", number of elements 6.3mm×12, inner diameter of the discharge port 1.5mm). The resulting thermally conductive composition (mass ratio 1:1) was applied to the demolding surface of a demolded PET film ("SG2" manufactured by Panack) in such a way that the thickness of the sample became 2mm, and another PET film ("SG2" manufactured by Panack) was pressed and fixed from above the sample in such a way that the demolding surface was in contact with the sample. After being placed at a temperature of 25°C and a humidity of 50% RH for 24 hours, sample 1A was obtained. The E-type hardness was measured using a material obtained by punching out 5 30mm square sheets from the obtained sample 1A and overlapping them, and the hardness was set as hardness E1.

[0362] The sample 2A obtained by the same method as above was put into a thermostatic bath set at 150°C and placed in the thermostatic bath for 250 hours. After being placed for 250 hours, the sample 2A was taken out of the thermostatic bath and cooled to 25°C, and the E-type hardness of the sample 2A was measured and set as hardness E2. In addition, the sample 2A-2 and the sample 3A obtained in the same manner except that the time placed in the thermostatic bath was changed to 500 hours and 1000 hours, the E-type hardness was measured and set as hardness E2-2 and hardness E3. From the obtained hardness E1, E2, and E3, E2 / E1 and hardness change (E3)-(E2-2) were also calculated.

[0363] In addition, the E-type hardness is measured by the E-type hardness tester of JIS K 6253.

[0364] [Thermal resistance of cured product of thermally conductive composition]

[0365] The first agent and the second agent were filled in a 50cc 2-liquid parallel cartridge (1:1 mixing cartridge "CDA050-01-PP" manufactured by MIXPAC), mixed using a static mixer (2-liquid mixing static mixer "MA6.3-12S", element number 6.3mm×12, discharge port inner diameter 1.5mm), and the obtained thermal conductive composition (mass ratio 1:1) was applied to the release surface of a release-treated PET film ("SG2" manufactured by Panac) so that the sample thickness was 0.5, 1.0, and 1.5mm, respectively, and another PET film ("SG2" manufactured by Panac) was pressed and fixed from above the sample so that the release surface was in contact with the sample. The sample was left at a temperature of 25°C and a humidity of 50%RH for 24 hours to obtain a sample 1B. The thermal resistance value (initial) of the obtained sample 1B was measured using a measuring device in accordance with ASTMD5470-06.

[0366] Sample 1B obtained by the same method as above was placed in a thermostatic bath set at 150°C and left there for 250 hours. Sample 2B after 250 hours was taken out of the thermostatic bath and cooled to 25°C, and then the thermal resistance value (after heating) was measured by the same method as above.

[0367] [Long-term heat resistance test]

[0368] The first agent and the second agent were filled in a 50cc 2-liquid parallel cylinder (1:1 mixing cylinder "CDA050-01-PP" manufactured by MIXPAC), and mixed using a static mixer (2-liquid mixing static mixer "MA6.3-12S", number of elements 6.3mm×12, inner diameter of the discharge port 1.5mm). The resulting thermally conductive composition (mass ratio 1:1) was fixed by sandwiching the flat surface side of the heat sink (a heat sink with 16 convex portions of 24mm height on one surface of a 60mm×60mm and 6mmt thick plate, material: aluminum) and the surface of the base (40mm×40mm and 10mmt thick, material: copper) with a spacer in a manner to make the thickness 1mm. At this time, the thermally conductive composition was set to 40mm×40mm×1mmt. Next, the thermally conductive composition was cured by placing it at a temperature of 25°C and a humidity of 50%RH for 24 hours to obtain a test sample.

[0369] Initially, the evaluation of the initial thermal resistance value using the above-mentioned sample was performed by the following method. A heater ("SCPU25×25" manufactured by Kashima Co., Ltd., size: 25×25mm, voltage / power: 100V / 100W) was set in the above-mentioned recess of the heat-insulating material (a 50mm×90mm plate with a thickness of 15mmt, material: HIPLA, in which a recess of 26mm×26mm and a depth of 1.7mm was formed in the center) and the back side of the base of the above-mentioned test sample was fixed thereon. At this time, in order to facilitate the transfer of heat from the heater to the sample (base), a 3W / m·K thermally conductive grease was placed between the surface of the heater and the back side of the above-mentioned base with a thickness of 50μm. In addition, a thermocouple was inserted into the insertion hole of the thermocouple set in the center of the above-mentioned heat sink and base, and was arranged in such a way that the front end of the thermocouple was directly above the center of the heater.

[0370] Next, a cooling fan was installed on the heat sink of the test sample, with an air volume of 0.53 m 3 / minute, and a wind pressure of 49Pa were used to supply air to the heat sink, and the resistance value of the heater before heating was confirmed. Then, the voltage was adjusted in such a way that the power of the heater became 100W. Furthermore, the temperature measured by the thermocouple on the heat sink side was set to T1, and the temperature measured on the base side was set to T2. The thermal resistance value R1 of the sample before the heat resistance test was calculated by the difference between T1 and T2 10 minutes after the start of heating by the heater and the heating power of the heater (thermal resistance value = (T1-T2) / 100). Then, the test sample that was cooled to room temperature after the voltage of the heater was set to 0 and the heating was stopped was removed from the insulation material and a thermal cycle test was performed. The thermal cycle test is to place it at -40°C for 30 minutes, then raise the temperature to 150°C and place it for 30 minutes as one cycle, and it was implemented for 1000 hours. Furthermore, after 1000 hours, the test sample was taken out from the constant temperature bath, and after it was placed until it reached room temperature, the thermal resistance value R2 after the thermal cycle test was calculated by the same steps as above.

[0371] Furthermore, the change (R2-R1) / R1×100(%) from the initial thermal resistance value R1 measured above to the thermal resistance value R2 after the thermal cycle test was calculated, and the degree of deterioration of the thermal resistance value was evaluated according to the following criteria.

[0372] A: (R2-R1) / R1×100 is 10% or less, and the reliability is good.

[0373] B: (R2-R1) / R1×100 is greater than 10% and less than 20%, and has reliability that can be used practically.

[0374] C: (R2-R1) / R1×100 is greater than 20%, indicating poor reliability.

[0375] D: Cannot be solidified and cannot be evaluated.

[0376] The raw materials used in the examples and comparative examples are as follows:

[0377] <Organopolysiloxane>

[0378] Organopolysiloxane 1 (component (A)): an organopolysiloxane having vinyl groups at both ends of the molecular chain (vinyl content: 0.17 mmol / g, viscosity: 410 mPa·s)

[0379] Organopolysiloxane 2 (component (A) and component (C)): a mixture of an organopolysiloxane having vinyl groups at both ends of the molecular chain (component (A)) and an organopolysiloxane having three or more hydrosilyl groups (component (C)) (vinyl content 0.15 mmol / g, hydrosilyl content 0.19 mmol / g, viscosity 336 mPa·s, mass ratio (component (A) : component (C)) = 95:5)

[0380] Organopolysiloxane 3 (component (A)): an organopolysiloxane having vinyl groups at both ends of the molecular chain (vinyl content: 0.136 mmol / g, viscosity: 1193 mPa·s)

[0381] Organopolysiloxane 4 (component (A) and component (C)): a mixture of an organopolysiloxane having vinyl groups at both ends of the molecular chain (component (A)) and an organopolysiloxane having three or more hydrosilyl groups (component (C)) (vinyl content 0.041 mmol / g, hydrosilyl content 0.06 mmol / g, viscosity 1034 mPa·s, mass ratio (component (A) : component (C)) = 95:5)

[0382] Organopolysiloxane 5 (component (A)): an organopolysiloxane having vinyl groups at both ends of the molecular chain (vinyl content: 0.69 mmol / g, viscosity: 1157 mPa·s)

[0383] (In organopolysiloxanes 2 and 4, component (A) does not have a hydrosilyl group, and component (C) does not have a vinyl (alkenyl) group.)

[0384] Organopolysiloxane 6 (component (B)): an organopolysiloxane having hydrosilyl groups at both ends of the molecular chain (hydrosilyl group content: 1.3 mmol / g, viscosity: 10 mPa·s)

[0385] Organopolysiloxane 7 (component (B)): an organopolysiloxane having hydrosilyl groups at both ends of the molecular chain (hydrosilyl group content: 0.333 mmol / g, viscosity: 100 mPa·s)

[0386] Organopolysiloxane 8 (component (B)): an organopolysiloxane having hydrosilyl groups at both ends of the molecular chain (hydrosilyl group content: 0.329 mmol / g, viscosity: 128 mPa·s)

[0387] Organopolysiloxane 9 (component (B)): an organopolysiloxane having hydrosilyl groups at both ends of the molecular chain (hydrosilyl group content: 0.116 mmol / g, viscosity: 1111 mPa·s)

[0388] Organopolysiloxane 10 (component (D)): an organopolysiloxane having a methacryloyl group at one end of the molecular chain (methacryloyl group content: 0.10 mmol / g, viscosity: 177 mPa·s)

[0389] Organopolysiloxane 11 (component (G-1)): dimethyl silicone oil having no hydrosilylation addition reaction group (viscosity 101 mPa·s)

[0390] Organopolysiloxane 12 (component (G-2)): an organopolysiloxane having no hydrosilylation addition reaction group and having a trialkoxysilyl group at the terminal (viscosity 26 mPa·s)

[0391] <Platinum group curing catalyst>

[0392] Platinum catalyst (component (F))

[0393] <Thermal conductive filler>

[0394] Alumina 1 ((E) component): spherical alumina (D50: 0.5 μm)

[0395] Alumina 2 ((E) component): spherical alumina (D50: 3 μm)

[0396] Alumina 3 ((E) component): spherical alumina (D50: 18 μm)

[0397] Alumina 4 ((E) component): spherical alumina (D50: 40 μm)

[0398] Alumina 5 ((E) component): spherical alumina (D50: 60 μm)

[0399] [Examples 1 to 12, Comparative Examples 1 to 7]

[0400] The first agent and the second agent were prepared according to the blending shown in the following Tables 1 to 3. Using the thermally conductive composition obtained by mixing the first agent and the second agent, various physical properties were measured and evaluated.

[0401] [Table 1]

[0402]

[0403] [Table 2]

[0404]

[0405] [Table 3]

[0406]

[0407] *Total Vi content 1 is the total content of alkenyl groups and methacryloyl groups relative to the total amount of organopolysiloxanes 1 to 10 in each of the first agent and the second agent.

[0408] * The total Vi content 2 is the total content of the vinyl group and the methacryloyl group relative to the total amount of the thermally conductive composition (the first agent and the second agent).

[0409] * The hydrosilyl group amount 1 is the content of the hydrosilyl group relative to the total amount of the organopolysiloxanes 1 to 10.

[0410] * The hydrosilyl group amount 2 is the content of the hydrosilyl group relative to the total amount of the thermally conductive composition (the first agent and the second agent).

[0411] The thermally conductive compositions of Examples 1 to 12 above contain components (A) to (F), and have a Raman intensity ratio p2 / p1 greater than 3.00. In addition, components (B) and (C) are mixed in such a manner that the hydrosilyl concentration ratio b / (b+c) is greater than 0.45. Furthermore, after being placed at 25°C for 24 hours and further at 150°C for 250 hours, the E-type hardness (E2) is less than 70. Therefore, the softness of the cured product can be well maintained even in an environment of 150°C, and the reliability is good. Therefore, even if the cured product of the thermally conductive composition is used as a thermally conductive component in a high-temperature environment, peeling relative to a heating element, a heat sink, etc. is suppressed, and an increase in thermal resistance is suppressed.

[0412] In contrast, the thermally conductive compositions of Comparative Examples 1 to 7 do not contain component (D), or the Raman intensity ratio p2 / p1 is 3.00 or less, and the components (B) and (C) are not mixed in such a manner that the hydrosilyl concentration ratio b / (b+c) is greater than 0.45. Therefore, in Comparative Examples 1 to 6, the softness of the cured product cannot be well maintained in an environment of 150°C or above, and the reliability is poor. Therefore, if the cured product of the thermally conductive composition is used as a thermally conductive component in an environment of 150°C or above, peeling occurs relative to a heating element, a heat sink, etc., and the increase in thermal resistance cannot be suppressed. In addition, in Comparative Example 7, poor curing occurred.

Claims

1. A thermally conductive composition comprising (A) an organopolysiloxane having two or more alkenyl groups, (B) an organohydrogenpolysiloxane having two hydrosilyl groups, (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups, (D) an organopolysiloxane having one alkenyl group or methacryloyl group, (E) thermally conductive filler material, and (F) a platinum group curing catalyst, 2160cm in Raman spectra -1 The Raman intensity p1 at 2130 cm -1 The Raman intensity p2 at satisfies the following relationship (1-1): After being placed at 25°C for 24 hours and further placed at 150°C for 250 hours, the E-type hardness E2 satisfies the following formula (2): p2 / p1>3.00 (1-1) E2<70 (2)。 2. A thermally conductive composition comprising (A) an organopolysiloxane having two or more alkenyl groups, (B) an organohydrogenpolysiloxane having two hydrosilyl groups, (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups, (D) an organopolysiloxane having one alkenyl group or methacryloyl group, (E) thermally conductive filler material, and (F) a platinum group curing catalyst, The component (B) and the component (C) are contained so as to satisfy the relationship of the following formula (1-2): The thermally conductive composition is placed at 25° C. for 24 hours and further at 150° C. for 250 hours, and the type E hardness E2 satisfies the following formula (2): b / (b+c)>0.45 (1-2) In formula (1-2), b is the concentration of the hydrosilyl groups contained in component (B), and c is the concentration of the hydrosilyl groups contained in component (C). E2<70 (2)。 3. A thermally conductive composition comprising (A) an organopolysiloxane having two or more alkenyl groups, (B) an organohydrogenpolysiloxane having two hydrosilyl groups, (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups, (D) an organopolysiloxane having one alkenyl group or methacryloyl group, (E) thermally conductive filler material, and (F) a platinum group curing catalyst, The thermally conductive composition is composed of a combination of a first agent and a second agent. The first agent comprises at least one of the components (A) and (D) and the component (F), and does not comprise the component (B) and the component (C). The second agent comprises the component (B) and the component (C), and does not comprise the component (F), 2160cm in Raman spectra -1 The Raman intensity p1 at 2130 cm -1 The Raman intensity p2 at satisfies the following relationship (1-1): After the first agent and the second agent are mixed and placed at 25°C for 24 hours, and further placed at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2): p2 / p1>3.00 (1-1) E2<70 (2)。 4. A thermally conductive composition comprising (A) an organopolysiloxane having two or more alkenyl groups, (B) an organohydrogenpolysiloxane having two hydrosilyl groups, (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups, (D) an organopolysiloxane having one alkenyl group or methacryloyl group, (E) thermally conductive filler material, and (F) a platinum group curing catalyst, The thermally conductive composition is composed of a combination of a first agent and a second agent. The first agent comprises at least one of the components (A) and (D) and the component (F), and does not comprise the component (B) and the component (C). The second agent comprises the component (B) and the component (C), and does not comprise the component (F), The component (B) and the component (C) are contained so as to satisfy the relationship of the following formula (1-2): After the first agent and the second agent are mixed and placed at 25°C for 24 hours, and further placed at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2): b / (b+c)>0.45 (1-2) In formula (1-2), b is the concentration of hydrosilyl groups in component (B), c is the concentration of hydrosilyl groups in component (C), E2<70 (2)。 5 . The thermally conductive composition according to claim 1 , further comprising (G) an organopolysiloxane having no addition reactive group. 6 . The thermally conductive composition according to claim 5 , wherein the component (G) comprises (G-2) an organopolysiloxane having at least one alkoxy group.

7. The thermally conductive composition according to any one of claims 1 to 6, wherein the relationship between the type E hardness E1 after being left at 25°C for 24 hours and the type E2 satisfies the following formula (3): 1.4≤E2 / E1≤3.5 (3). 8 . The thermally conductive composition according to claim 1 , wherein the component (D) is an organopolysiloxane having one methacryloyl group. 9 . The thermally conductive composition according to claim 1 , wherein the total content of the alkenyl group and the methacryloyl group is 5.0 μmol / g or less.

10. The thermally conductive composition according to any one of claims 1 to 9, wherein the content H of the hydrosilyl group and the total content Vi of the alkenyl group and the methacryloyl group satisfy the relationship of the following formula (4): 0.85≤H / Vi≤1.1 (4). 11 . A thermally conductive member obtained by curing the thermally conductive composition according to claim 1 .

12. A first agent which can be used as a thermally conductive composition by mixing with a second agent, the thermally conductive composition comprising (A) an organopolysiloxane having two or more alkenyl groups, (B) an organohydrogenpolysiloxane having two hydrosilyl groups, (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups, (D) an organopolysiloxane having one alkenyl group or methacryloyl group, (E) thermally conductive filler material, and (F) a platinum group curing catalyst, The first agent comprises at least one of the components (A) and (D) and the component (F), and does not comprise the component (B) and the component (C). The first agent is combined with the second agent to obtain a Raman spectroscopic spectrum at 2160 cm -1 The Raman intensity p1 at 2130 cm -1 The Raman intensity p2 at satisfies the following relationship (1-1): After the first agent and the second agent are mixed and placed at 25°C for 24 hours, and further placed at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2): p2 / p1>3.00 (1-1) E2<70 (2)。 13. A second agent which can be used as a thermally conductive composition by mixing with a first agent, the thermally conductive composition comprising (A) an organopolysiloxane having two or more alkenyl groups, (B) an organohydrogenpolysiloxane having two hydrosilyl groups, (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups, (D) an organopolysiloxane having one alkenyl group or methacryloyl group, (E) thermally conductive filler material, and (F) a platinum group curing catalyst, The second agent comprises the component (B) and the component (C), and does not comprise the component (F), The second agent is combined with the first agent to obtain a Raman spectroscopic spectrum at 2160 cm -1 The Raman intensity p1 at 2130 cm -1 The Raman intensity p2 at satisfies the following relationship (1-1): After the first agent and the second agent are mixed and placed at 25°C for 24 hours, and further placed at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2): p2 / p1>3.00 (1-1) E2<70 (2)。 14. A first agent which can be used as a thermally conductive composition by mixing with a second agent, the thermally conductive composition comprising (A) an organopolysiloxane having two or more alkenyl groups, (B) an organohydrogenpolysiloxane having two hydrosilyl groups, (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups, (D) an organopolysiloxane having one alkenyl group or methacryloyl group, (E) thermally conductive filler material, and (F) a platinum group curing catalyst, The first agent comprises at least one of the components (A) and (D) and the component (F), and does not comprise the component (B) and the component (C). The thermally conductive composition contains the component (B) and the component (C) so as to satisfy the relationship of the following formula (1-2). After the first agent and the second agent are mixed and placed at 25°C for 24 hours, and further placed at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2): b / (b+c)>0.45 (1-2) In formula (1-2), b is the concentration of hydrosilyl groups in component (B), c is the concentration of hydrosilyl groups in component (C), E2<70 (2)。 15. A second agent which can be used as a thermally conductive composition by mixing with a first agent, the thermally conductive composition comprising (A) an organopolysiloxane having two or more alkenyl groups, (B) an organohydrogenpolysiloxane having two hydrosilyl groups, (C) an organohydrogenpolysiloxane having three or more hydrosilyl groups, (D) an organopolysiloxane having one alkenyl group or methacryloyl group, (E) thermally conductive filler material, and (F) a platinum group curing catalyst, The second agent comprises the component (B) and the component (C), and does not comprise the component (F), The component (B) and the component (C) are contained so as to satisfy the relationship of the following formula (1-2): After the first agent and the second agent are mixed and placed at 25°C for 24 hours, and further placed at 150°C for 250 hours, the type E hardness E2 satisfies the following formula (2): b / (b+c)>0.45 (1-2) In formula (1-2), b is the concentration of hydrosilyl groups in component (B), c is the concentration of hydrosilyl groups in component (C), E2<70 (2)。